2015
DOI: 10.12688/f1000research.6890.1
|View full text |Cite
|
Sign up to set email alerts
|

Fascial Manipulation® for chronic aspecific low back pain: a single blinded randomized controlled trial

Abstract: Background: The therapeutic approach to chronic aspecific low back pain (CALBP) has to consider the multifactorial aetiology of the disorder. International guidelines do not agree on unequivocal treatment indications. Recommendations for fascial therapy are few and of low level evidence but several studies indicate strong correlations between fascial thickness and low back pain. This study aims at comparing the effectiveness of Fascial Manipulation® associated with a physiotherapy program following guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
(5 reference statements)
0
23
0
Order By: Relevance
“…The search process is reported in Figure 1. Of 513 records, finally 8 were considered relevant for qualitative analysis 21 28 (Figure 1 and Supplementary Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The search process is reported in Figure 1. Of 513 records, finally 8 were considered relevant for qualitative analysis 21 28 (Figure 1 and Supplementary Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The duration of follow-up ranged from immediate assessment after the end of treatment 28 up to one year. 27 The risk of bias was considered high in five of eight trials 2123,25,28 (Supplementary Table 3). Three RCTs were conducted in the outpatient clinic of Myofascial Therapy and Research Foundation, 21 23 two samples involved the members of Fibromyalgia Association, 26,27 one sample was gathered in a physiotherapy outpatient department, 28 and two in tertiary outpatient clinics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study reported that successful average NRS changes (2.66) in lumbar spine surgery patients are well above the minimal clinically important difference (MCID) range (0.28-4.5) [40][41][42][43][44]. The NRS difference in this study from baseline to 7 weeks was 3.02, which is a meaningful value compared with other studies and is in the MCID range.…”
Section: Discussionmentioning
confidence: 41%